1027. Outpatient Parenteral Antimicrobial Therapy (OPAT) in Injection Drug Users (IDUs): Is It Safe?. (26th November 2018) - Rizvi, Hira; Baratz, Nathalie; Hadid, Hind; Bardossy, Ana C; Herc, Erica; Misikir, Helina; Chen, Anne; Markowitz, Norman; Zervos, Marcus J
Abstract: Background: OPAT is widely implemented in the United States. However, there are concerns surrounding discharge of IDU with a peripherally inserted central catheter (PICC). The objective of this study was to evaluate the characteristics and treatment outcomes of IDUs discharged on OPAT. Methods: This is a retrospective observational study conducted on patients discharged from an Infectious Diseases unit at a quaternary academic healthcare center in Detroit. Charts of all IDUs discharged on OPAT between 2011 and 2017 were reviewed. Current or former IDU were discharged on OPAT if they met the following criteria: self-reported history of IDU, stable living conditions, controlled psychiatric illness (if present), and willingness to sign a discharge agreement to refrain from using the PICC as a route for illicit drugs. Patients were categorized based on clinic follow-up vs. no clinic follow-up. Outcomes evaluated were: cured (completed treatment and symptom free for 1 month after completion), improved (symptoms were improved but there was no confirmation of treatment completion); and relapsed (readmitted within 30 days for the same infection or sequela). Outcomes of patients with no clinic follow-up were based on chart review of subsequent emergency department visits or admissions. Results: Patient characteristics are shown in Table 1. Of the 61 patients evaluated, 33 (54.1%) attended clinic follow-up and 28 (45.9%) did not. Outcomes based on clinic follow-up are shown in Table 2. Of the 18 patients who were cured, 16 attended clinic follow-up vs. two who did not. Conclusion: This study demonstrates that some IDUs can be discharged safely on OPAT. Patients with clinic follow-up had improved outcomes compared with those who did not. Further studies are needed to look at other predictors of outcome in this patient population. Disclosures: All authors: No reported disclosures.